OBE-Based Monitoring of Graduate Learning Outcomes in INSPIRE Managerial Application - Rumbajan, Wemfrits Christian; Sambul, Alwin; Paturusi, Sary (Jurnal Teknik Elektro dan Komputer, 2026)
Monitoring Program Learning Outcomes (CPL/PLO) is essential in the Outcome-Based Education (OBE) quality assurance cycle, as it supports curriculum evaluation and continuous improvement. Common challenges include fragmented attainment data, limited visualization, and difficulty tracing course contributions down to CPMK, Sub-CPMK, and assessment evidence. This paper presents the design of a CPL monitoring dashboard in the INSPIRE Manajerial application at Universitas Sam Ratulangi. The dashboard is designed to list CPL items by curriculum, expand into supporting courses with contribution weights, provide hierarchical views down to CPMK and Sub-CPMK with progress indicators, and display radar charts that depict the contribution/attainment profile of a course across multiple CPL items on a 0-100 scale. The design also includes per-student CPL monitoring to support academic decision-making. The resulting multi-layer visualization and drill-down capability provide real-time transparency for study program coordinators and quality assurance teams to detect attainment gaps, review weighting, and formulate data-driven improvement actions.